2005
DOI: 10.1113/jphysiol.2004.076927
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐mediated control of hypocretin‐ but not melanin‐concentrating hormone‐immunoreactive neurones during sleep in rats

Abstract: The perifornical-lateral hypothalamic area (PF-LHA) has been implicated in the regulation of behavioural arousal. The PF-LHA contains several cell types including neurones expressing the peptides, hypocretin (HCRT; also called orexin) and melanin-concentrating hormone (MCH). Evidence suggests that most of the PF-LHA neurones, including HCRT neurones, are active during waking and quiescent during non-rapid eye movement (non-NREM) sleep. The PF-LHA contains local GABAergic interneurones and also receives GABAerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
99
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 51 publications
13
99
1
Order By: Relevance
“…These data are comparable with those obtained by Alam et al (Alam, et al, 2005), which demonstrated that the majority of neurons expressing Fos during active waking induced by bicuculline application into the lateral hypothalamus of the rat were non-hypocretinergic nonMCHergic neurons (ibid.). The postero-lateral and adjacent hypothalamic areas are known to be involved in the control of motor activity.…”
Section: Discussionsupporting
confidence: 90%
“…These data are comparable with those obtained by Alam et al (Alam, et al, 2005), which demonstrated that the majority of neurons expressing Fos during active waking induced by bicuculline application into the lateral hypothalamus of the rat were non-hypocretinergic nonMCHergic neurons (ibid.). The postero-lateral and adjacent hypothalamic areas are known to be involved in the control of motor activity.…”
Section: Discussionsupporting
confidence: 90%
“…During sleep, orexin neurons would be inhibited by GABAergic influences from neurons in the preoptic area (1), which are likely important for stably silencing orexin neurons (33,34). In oxGKO mice, both GABA A -and GABA B -mediated inhibition of orexin neurons was severely impaired (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Single unit recording studies suggest that the orexin neurons exhibited the Wake-On/REM -Off discharge pattern (W>nonREM<REM) (Alam et al, 2002;Lee et al, 2005;Mileykovskiy et al, 2005). The δ-subunit-containing GABA A receptors are present in the PFH (Pirker et al, 2000) and the role of PFH GABA A receptors in sleep induction has been previously shown (Alam et al, 2004). However, it is yet unclear whether extrasynaptic GABA A receptors in the PFH have any role in control of sleep-wakefulness.…”
mentioning
confidence: 98%
“…Although the PFH contains several cell types, including the orexin/hypocretin and the melanin concentrating hormone containing neurons, there is compelling and consistent evidence implicating the orexins neurons in the control of wakefulness (McCarley, 2007). For example, local administration of orexin in various brain regions produced wakefulness (Bourgin et (Pirker et al, 2000) and the role of PFH GABA A receptors in sleep induction has been previously shown (Alam et al, 2004). However, it is yet unclear whether extrasynaptic GABA A receptors in the PFH have any role in control of sleep-wakefulness.…”
mentioning
confidence: 99%